PENYELESAIAN SENGKETA BATAS ANTAR DAERAH - Andre Junianto Patongloan (Universitas Borneo Tarakan, 2019)
Abstract Inter-regional Border Dispute Resolution by Andre Junianto Patongloan and guided by Dr. Marthen B. Salinding, Salinding, SH, MH and Dr. Basri, SH, M.Kn. In a study of this, the formulation of the problem that is raised among others: 1. Urgency Affirmation of Region in the Formation of Territory, 2. Efforts Law Against Settlement Dispute Regional Boundaries. The study is intended to examine is normative and examine the issue of the legal use of the principles of law as well as by using a methodology approach to regulation law - law (statue approach) and the approach of the case (case approach). That regional autonomy is a promising manifestation for the region, which is tight relation to the boundaries of the area that was in the area of autonomous mentioned. Problems boundary area has a dimension that is very complex, such as; conflict social, conflict sources of the power of nature, conflict ethnicity /culture /ethnicity and so forth. Completion tiered by the Governor and the Minister in the State, is a form of public law in the name of the state. The role of the Governor and the Minister in the State shows the behavior of an active state, as affirmed in the principle of the modern state. Form of settlement of disputes boundary region between regions as part of the implementation of the functions of government found their Autonom organs of government ( vrijbevoegdheid), discretionary or Freiesermessen ), this is because the regulatory legislation that no-load norms are vague ( voge norm), the norm is open (open norm ) or contains a choice (choice) . In this case, it must be understood that what is done by a government organ is not in a capacity as a function of hearing or as a function of legislation. Settlement of disputes boundary region between regions that pursued by the mechanism of the law of the country through the agency of justice which there has been expected to provide legal certainty and a sense of justice. In preventing the confusion of the conflict norm on several levels of regulation law for the settlement of disputes boundary region between regions. the principle of cooperation between regions can be relied upon to translate legal certainty and provide a sense fair for the government area to organize and manage the limits of its territory as one of the supporting creation of the implementation of the autonomous regions that good.Keyword: Establishment of Regional, Local Limits, Settlement Dispute.